2019
DOI: 10.1038/s41598-019-53125-1
|View full text |Cite
|
Sign up to set email alerts
|

Chern and Z2 topological insulating phases in perovskite-derived 4d and 5d oxide buckled honeycomb lattices

Abstract: Based on density functional theory calculations including a Coulomb repulsion parameter U, we explore the topological properties of (LaXO3)2/(LaAlO3)4 (111) with X = 4d and 5d cations. The metastable ferromagnetic phases of LaTcO3 and LaPtO3 with preserved P321 symmetry emerge as Chern insulators (CI) with C = 2 and 1 and band gaps of 41 and 38 meV at the lateral lattice constant of LaAlO3, respectively. Berry curvatures, spin textures as well as edge states provide additional insight into the nature of the CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Model Hamiltonian studies in conjunction with DFT calculations predicted a distinct set of four bands in (111) bilayers of LaNiO , two nearly flat interconnected by two dispersive ones with a Dirac crossing at and a quadratic band touching at 8 11 . Systematic DFT+ U calculations have shown that this set of bands occurs also for La X O ( Mn and Co 12 ) and a Chern insulator phase driven by spin-orbit coupling (SOC) can emerge in (111) bilayers of La X O ( Mn 12 , 13 , Co 12 , Ru, Os 14 , Pd, and Pt 15 , 16 ). The (111)-oriented LaMnO buckled honeycomb bilayer was predicted to have a nontrivial band gap of 150 meV and a quantized anomalous Hall conductivity of 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Model Hamiltonian studies in conjunction with DFT calculations predicted a distinct set of four bands in (111) bilayers of LaNiO , two nearly flat interconnected by two dispersive ones with a Dirac crossing at and a quadratic band touching at 8 11 . Systematic DFT+ U calculations have shown that this set of bands occurs also for La X O ( Mn and Co 12 ) and a Chern insulator phase driven by spin-orbit coupling (SOC) can emerge in (111) bilayers of La X O ( Mn 12 , 13 , Co 12 , Ru, Os 14 , Pd, and Pt 15 , 16 ). The (111)-oriented LaMnO buckled honeycomb bilayer was predicted to have a nontrivial band gap of 150 meV and a quantized anomalous Hall conductivity of 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Further candidates for quantum anomalous Hall insulators (QAHI) are LaRuO 3 and LaOsO 3 24 , as well as the metastable symmetric ferromagnetic cases of LaPdO 3 , LaPtO 3 and LaTcO 3 25,26 honeycomb bilayers encased in LaAlO 3 (111). Corundum-derived SL provide another realization of the honeycomb lattice.…”
Section: Introductionmentioning
confidence: 99%